Mean platelet volume increases in proliferative retinopathy among diabetes mellitus subjects - Mardiya Sari; Dharma Lindarto; Dairion Gatot (Universa Medicina, 2014)
BACKGROUND Mean platelet volume (MPV) shows the average size of platelets in the circulation and can be used to assess the activity of platelets. Increased of MPV can be sign of atherotrombosis and can be used to assess the risk of vascular complications such as retinopathy diabetic (RD). The aim of this study was to determine correlation between glycated haemoglobin (HbA1c), MPV with degree of retinopathy in diabetes mellitus (DM) patients. METHODS A cross sectional study from June until July 2013 was conducted involving 77 DM subjects. Anamnesis, laboratory examination and funduscopy had been done in all subjects. One way ANOVA was used to assess the differences between MPV with other parameters to the degree of retinopathy and continued with Bonferroni test to assess the differences between the degree of retinopathy with the parameters that significantly different in one way ANOVA. RESULTS One way ANOVA showed significance difference of mean MPV between normal funduscopy group compared than proliferative diabetic retinopathy (PDR) group (9.57 ± 0.63 fl vs 10.45 ± 0.51 fl, p=0.044). PDR group were older (p=0.001), longer suffered from DM (p=0.001) and hypertension (p=0.011). Bonferroni test showed no significance difference of mean MPV between normal funduscopy versus non-proliferative diabetic retinopathy (NPDR) group (p=0.290) and NPDR versus PDR (p=0.409). CONCLUSION There was a significance differences between MPV with the degree of retinopathy. Platelets may play a role in the pathogenesis of vascular complications and that MPV can be used as simple parameter to assess the vascular events in DM.